Evaluation Implementation of the Arabic Language Intensification Program (PIBA) in Islamic Higher Education - Isbah, Faliqul; Rosyid, M. Fairuz; Tamama, Nilna Uswah (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This article discusses the evaluation of the implementation process of the Arabic Language Intensification Program (PIBA) at UIN K.H. Abdurrahman Wahid Pekalongan, analyzes student responses to the program, and explores their expectations regarding the Arabic language learning method at the higher education level. The research approach is qualitative evaluative, aimed at assessing the implementation of the intensive Arabic language program. The evaluation model used is Stake’s Model, which includes three stages: Antecedents (background), Transaction (process), and Outcomes (results). Data were collected from primary sources (teachers and students) and secondary sources (placement test scores, final program grades, and satisfaction survey reports). Data collection was carried out through observation, interviews, and documentation. The results indicate that the program improves Arabic language proficiency, particularly for students with a general education background, although challenges such as varying effectiveness and the need to improve tutor planning remain. Final grades were generally positive, but students expressed a desire for more speaking practice, a more suitable schedule, representative classes, and more varied and interactive teaching methods.